Comparison of the effectiveness of physical training and extract of soursop leaf to histopathology of abdominal aorta foam cells in hipercolesterolemia-diabetes rat - Tika Hamidah Apriliana Nai; Retno Yulianti; Wahyunia Likhayati Septiana; Yuni Setyaningsih (Acta Biochimica Indonesiana, 2020)
Background: Diabetes mellitus has become a public health problem globally. Type 2 diabetes mellitus, caused by lifestyle and high lipid diet, is the most common form. Hypercholesterolemia-diabetes is able to create endothelial injury that results in formation of atherosclerosis, starting with formation of foam cells. Objective: This research aimed to see the effectiveness of physical training and soursop (Annona muricata) leaves extract in lowering the amount of foam cells. Methods: This research was an experimental study which used the post test-only control group design with 35 Wistar strain rats which were randomly divided into 7 groups, each consisting of 5 rats. K1 was given standard diet, K2 was given atherogenic diet and alloxan, while K3, K4, K5, K6, and K7 were given atherogenic diet, alloxan, and different treatments based on designed group. K3 was given simvastatin, K4 was given metformin, K5 was given physical training, K6 was given soursop leaves extract (SLE), and K7 was given both physical training and SLE. The rats were euthanized after three weeks and aorta was taken to be made into histology slides for foam cells observation. Results: The result of Kruskal-Wallis and Mann-Whitney Post-Hoc Test showed significant difference (p<0,05) between K2 and K5, K6, K7 while it no significant difference (p>0,05) between K3, K4 and K5, K6, K7. Conclusion: Physical training, SLE, and the combination of both have a role in lowering formation of foam cells in atherosclerosis.